THE SPECIAL ROLE OF THE g -FUNCTIONS - Valera, Dhurata; Dylgjeri, Ivi (Matematichki Bilten, 2014)
The class of \(g\)-functions by the \(g\)-generator of the system of pseudo-operations, apply a special role on functional equations and their solutions. More properties may be found in this class and by some elementary \(g\)-functions are given further studies to the entropy of \(\)-(decomposable) measure.